The Perception of Needs in End Stage Renal Disease Patients and Caregivers for Palliative care: Phenomenological Study - Artsanthia, Jintana; Noppornpun, Mayura; Mungsungnen, Sayfon; Teeradetchachart, Parichat; Amaridchatchawan, Saychol (Journal of The Royal Thai Army Nurses, 2021)
This phenomenological study had objectives to 1). Study perception of illness with end stage renal disease 2). Study of perception in palliative care of patient and caregivers, and 3). study the needs of palliative care of patient and family. The sample were 25 patients and caregivers. Data collection composed of in-depth interview, focus group and observe without participation. The questionnaire had CVI 0.81 by passing the 3 experts. Data analysis was used by content analysis. The result found that the perception and the meaning of end stage renal disease composed of suffering disease, need to deeply understand and try to live with this disease. The problems from the disease composed of loss money, lead to be alone, encounter with many problems from disease. The perceptions of the body were stable and worse if good care it will be fine if not will lead to die, need to get hemodialysis, uncomfortable with the symptom. Moreover, the patient perceived pain as normal and natural thing that they coped, some of them wanted to die without treatment. The factors affected to quality of life composed of budget in treatment, loss of the role, relationship of family.